One-year follow-up in patients with brainstem infarction due to large-artery atherothrombosis - Kolukısa M, Ozdemir Gültekin T (Dove Medical Press, 2015)
Mehmet Kolukisa,1 Tugce Ozdemir Gültekin,1 Gozde Eryigit Baran,1 Ayse Aralasmak,2 Gülsen Kocaman,1 Azize Esra Gürsoy,1 Talip Asil1 1Department of Neurology, 2Department of Radiology, Faculty of Medicine, Bezmialem Vakif University, Istanbul, Turkey Background: Posterior circulation infarction accounts for approximately 25% of the ischemic strokes. A number of different conditions may be associated with the development of brainstem infarction. Prognosis and recurrence rate of brainstem infarction due to large-artery atherothrombosis is still controversial. Methods: A total of 826 patients with ischemic stroke were admitted to our clinic during a 15-month period. Patients with clinical and radiological evidence of brainstem infarction were comprehensively assessed with appropriate vascular imaging modalities and for cardiological causes. Subjects with an established diagnosis of large-artery atherothrombosis were followed up for 1 year in terms of prognosis and recurrence rates. Results: Of the 101 patients with an established brainstem infarction, the diagnostic work-up indicated the presence of large-artery atherothrombosis as the causative factor in 53. A recurrent stroke was detected in the posterior circulation within the first 3 months in 5.8% and within 1 year in 9.8% of these individuals. The 1-year mortality rate was 11.7%. All patients with recurrent stroke had intracranial vascular narrowing at baseline. Conclusion: Our findings demonstrate a particularly high rate of recurrence and mortality at 1 year among patients who have a brainstem infarction due to intracranial arterial stenosis. Keywords: posterior circulation, intracranial arteries, extracranial arteries, stroke, vertebral artery, basilar artery